What is the volume, diversity and nature of recent, robust evidence for the use of peer support in health and social care? An evidence and gap map - Anna Price; Siân deBell; Naomi Shaw; Alison Bethel; Rob Anderson; Jo Thompson Coon (Campbell Systematic Reviews, 2022)
Abstract Background Peer support interventions involve people drawing on shared personal experience to help one another improve their physical or mental health, or reduce social isolation. If effective, they may also lessen the demand on health and social care services, reducing costs. However, the design and delivery of peer support varies greatly, from the targeted problem or need, the setting and mode of delivery, to the number and content of sessions. Robust evidence is essential for policymakers commissioning peer support and practitioners delivering services in health care and community settings. This map draws together evidence on different types of peer support to support the design and delivery of interventions. Objectives The aim of this map was to provide an overview of the volume, diversity and nature of recent, high quality evidence on the effectiveness and cost‐effectiveness of the use of peer support in health and social care. Search Methods We searched MEDLINE, seven further bibliographic databases, and Epistemonikos for systematic reviews (in October 2020), randomised controlled trials (in March 2021) and economic evaluations (in May 2021) on the effectiveness of peer support interventions in health and social care. We also conducted searches of Google Scholar, two trial registers, PROSPERO, and completed citation chasing on included studies. Selection Criteria Systematic reviews, randomised controlled trials and economic evaluations were included in the map. Included studies focused on adult populations with a defined health or social care need, were conducted in high‐income countries, and published since 2015. Any measure of effectiveness was included, as was any form of peer support providing the peer had shared experience with the participant and a formalised role. Data Collection and Analysis Data were extracted on the type of peer support intervention and outcomes assessed in included studies. Standardised tools were used to assess study quality for all studies: assessing the methodological quality of systematic reviews 2 for systematic reviews; Cochrane risk of bias tool for randomised controlled trials; and consensus health economic criteria list for economic evaluations. Main Results We included 91 studies: 32 systematic reviews; 52 randomised controlled trials; and 7 economic evaluations. Whilst most included systematic reviews and economic evaluations were assessed to be of low or medium quality, the majority of randomised controlled trials were of higher quality. There were concentrations of evidence relating to different types of peer support, including education, psychological support, self‐care/self‐management and social support. Populations with long‐term health conditions were most commonly studied. The majority of studies measured health‐related indicators as outcomes; few studies assessed cost‐effectiveness. Studies were unevenly distributed geographically, with most being conducted in the USA. Several gaps were evident regarding the delivery of peer support, particularly the integration of peers and professionals in delivering support and interventions of longer duration. Authors' Conclusions Although there is evidence available to inform the commissioning and delivery of peer support in health and social care, there are also clear gaps that need to be addressed to further support provision, particularly regarding cost‐effectiveness. The effectiveness of peer support in different countries, with varying health and social care systems, is a priority for future research, as is the integration of peers with professionals in delivering peer support.